Simulation of respiratory flows - Mead-Hunter, R.; King, Andrew; Larcombe, A.; Mullins, B. (2014)
Simulations were conducted on the respiratory tract of a juvenile rhesus monkey, to determine if turbulence modelling is required in such simulations. Simulations were conducted using two different breathing rates and both laminar and turbulent flow models. The analysis was complicated by the complexity of the geometry and the nature of the flow. Given the pulsatile nature of the flow, a lower Reynolds number for transition was applied, based on experimental work in the literature. We have found that at higher breathing rates there is a need for a turbulence model.